Improvement Of Scientific Work Writing In English With The Task-Based Language Teaching Method In The English Education Program - Hasbi, Muhammad; Inayah, Nur; Latif, Fatmawati; Mutmainna; Fahira, Ainun (Education and Talent Development Center of Indonesia, 2022)
The goal of this community service is to apply the Task-Based Language Teaching (TBLT) technique in writing scientific articles to improve the writing skills of students in the English Education Study Program. Classroom Action Research (CAR) was used in this study, which was divided into two cycles. Thirty students who took the Introduction to Thesis Writing course were used as research subjects. Direct measurement and observation are used to acquire data. Tests and observation sheets are used as data collection instruments. Data triangulation was utilized as a data analysis tool. The findings revealed that: (1) the TBLT method has been shown to increase student learning activities, interaction in learning, and student independence; (2) the average ability of students in writing scientific papers has increased from 5.21 in the first cycle to 7.1 in the second cycle; and (3) the teaching and learning process of writing scientific papers has become more meaningful, interesting, and fun.